Preprecevanje prekomerne izgube vode v telesu med vadbo na zmerni višini s pravilno hidracijo - Štrumbelj, B. (Kinesiologia Slovenica, 2018)
The concept of altitude training is a widespread practice in swimming. The mountain conditions of most altitude venues are characterized by cold and dry air, which leads to an increased loss of water with increased pulmonary ventilation. There are indications that the body composition of athletes who are exposed to high altitudes may change significantly after exercise. The aim of the study was to experimentally test with Bioelectrical Impedance Analysis (BIA) to find if athletes with proper hydration and dietary restrictions can prevent excessive water loss during training at moderate-altitudes. The survey included 14 women (16.6 ± 1.2 years) and 6 men (19.2 ± 3.0 years), members of the national swimming team. All BIA measurements were carried out before, and four times during the twenty-one-day swim camp at moderate altitude as well as after altitude exposure. There were no statistically significant differences found with ANOVA between the measured or calculated body weight, the amount of body fluid, and the amount of body fluid in terms of body weight in % for men or for women. The results of our study show that adequate water replacement (up to 3 litres per day depending on the needs) and diet can prevent dehydration during training at a moderate altitude. The BIA seems to be a useful tool for measuring the amount of body fluid in swimmers. Measurements with the help of BIA are acceptable for use, although the amounts of body fluid obtained with BIA appear to be overestimated in terms of other methods of measuring the amount of body fluid.